Fostering Entrepreneurship Among Millennials: A Systematic Literature Review Of Trends, Challenges, And Opportunities - Nissa Ghulma Ratnasari (Riviera Publishing, 2025)
Entrepreneurship has become a major driver of economic growth and innovation in the modern era. The millennial generation, which is the largest group in the workforce today, has great potential to become successful entrepreneurs. However, they also face unique challenges in starting and growing businesses. This study aims to conduct a systematic review of the literature on trends, challenges, and opportunities in fostering entrepreneurship among millennials. By analyzing the results of previous research, this study seeks to provide a better understanding of how to facilitate and support millennial entrepreneurship, as well as identify areas of advanced research needed to improve the success of millennial entrepreneurs. The initial search keyword series is